A New Spectrofluorimetric Approach for The Quantitation of Imipramine Hcl in Commercial Dosage Forms - Syed, Najmul Hejaz Azmi; Manal, Khalifa Al-Hattali; Ruiyah, Khalifa Al-Hinai; Ibtihal, Mohammed Al-Ajmi (Journal of Advanced Pharmaceutical Science And Technology, 2017)
A spectrofluorimetric method has been developed for the determination of imipramine HCl in bulk and commercial dosage forms. The method was based on measuring the fluorescence emission intensity of imipramine-eosin Y ion pair complex (λem = 558 and λex = 319) in dichloroethane at buffer solution (sodium acetate and acetic acid) of pH 4.8. The stoichiometric ratio between imipramine and eosin Y was studied by Job's method of continuous variations and found to be 2:1. Formation constant (Kf) and Gibb’s free energy change (ΔG) were calculated and pointed towards the spontaneous nature of the reaction. A series of variables were studied to optimize the reaction conditions. The proposed method was validated as per ICH guidelines and successfully applied for the determination of active imipramine HCl in commercial dosage forms with high degree of accuracy and precision.
Keywords: imipramine HCl; spectrofluorimetry; validation; ICH guideline; commercial dosage forms